Concept of Coastal Abrasion Disaster Risk Management - Haslimin Haslimin; Natsar Desi; Muhammad Chaerul (Journal La Lifesci, 2026)
This study aims to analyze the hydro-oceanographic characteristics, identify the natural and anthropogenic factors causing coastal abrasion, assess the level of abrasion impact, and formulate an appropriate coastal abrasion management concept in the Batauga coastal area, South Buton Regency. A descriptive field-survey approach supported by hydro-oceanographic analysis and qualitative assessment was employed. Primary data were collected through bathymetric measurement, tidal observation, current measurement, field observation, documentation, and semi-structured interviews with relevant stakeholders. Bathymetric data were obtained using a GPS-integrated echosounder, tidal data were analyzed using the least squares method, and current velocity was calculated based on buoy displacement and validated with a digital current meter. The results show that the Batauga coast has a gentle bathymetric profile, allowing wave energy from the Flores Sea to reach the shoreline with limited attenuation. The mixed prevailing semidiurnal tidal pattern expands the active intertidal zone, while longshore currents contribute to sediment transport and sediment imbalance. In addition, illegal sand mining significantly accelerates abrasion by reducing sediment volume and altering seabed morphology. The level of abrasion impact is categorized as high, as indicated by shoreline retreat, seabed degradation, scouring around coastal structures, infrastructure vulnerability, and ecosystem damage. Therefore, a hybrid coastal protection system combining structural measures, non-structural strategies, vegetation rehabilitation, sediment stabilization, and strict control of sand mining activities is recommended for sustainable abrasion management in Batauga.